A literature survey of the robotic technologies during the COVID-19 pandemic. (July 2021) - Wang, Xi Vincent; Wang, Lihui
Highlights: The recent robot technologies are thoroughly surveyed from the COVID-19 pandemic's perspective. 280 scientific documents are surveyed and 146 of them are discussed in details. The main robotic research contributions are categorised in 11 types and systematically analysed. The promising supporting technologies are identified for future research during and after the pandemic. Abstract: Since the late 2019, the COVID-19 pandemic has been spread all around the world. The pandemic is a critical challenge to the health and safety of the general public, the medical staff and the medical systems worldwide. It has been globally proposed to utilise robots during the pandemic, to improve the treatment of patients and leverage the load of the medical system. However, there is still a lack of detailed and systematic review of the robotic research for the pandemic, from the technologies' perspective. Thus a thorough literature survey is conducted in this research and more than 280 publications have been reviewed, with the focus on robotics during the pandemic. The main contribution of this literature survey is to answer two research questions, i.e. 1) what the main research contributions are to combat the pandemic from the robotic technologies' perspective, and 2) what the promising supporting technologies are needed during and after the pandemic to help and guide future robotics research. The current achievements of robotic technologies are reviewed and discussed in different categories, followed by the identification of the representative work's technology readiness level. The future research trends and essential technologies are then highlighted, including artificial intelligence, 5 G, big data, wireless sensor network, and human-robot collaboration.